The Evaluation of Field Teaching Practice Using Kirkpatrick’s Model - Asnan Purba; Amri Dhimas Maulana (Universitas Negeri Yogyakarta, 2023)
This study aims to evaluate a Field Teaching Practice program carried out by students of the social studies education study program at the Tazkia Islamic University College using the Kirkpatrick model, which includes reaction, learning, behavior, and result. The research method used is a descriptive approach with an evaluation of Kirkpatrick's model. The subject of this research used purposive sampling. Data collection techniques using observation, in-depth interview, and documentation. The data analysis technique in this study used an interactive model. The results: 1) Evaluation at level one (reaction) show that students already responded positively, enthusiastically, and happy in implementing Field Teaching Practice because it was equipped with micro-teaching to facilitate the implementation process. (2) Second level evaluation (learning) shows that only a few students can achieve the target in the learning process in class. Unable to meet the target due to the limited time and infrastructure constraints hinder the learning process. (3) Third level evaluation (behavior) shows that students' change in behavior is seen from how students are increasingly proficient and their confidence increases when dealing with students. (4) The fourth level results from student satisfaction with Field Teaching Practice sustainability; most students are mature and ready to become teachers after graduation because with this Field Teaching Practice, in addition to getting experience as a teacher, they can also know the world of education comprehensivelyKeywords: Evaluation, Field Teaching Practice, Kirkpatrick’s Model